2003
DOI: 10.1128/cdli.10.3.443-445.2003
|View full text |Cite
|
Sign up to set email alerts
|

Immunohematological Reference Ranges for Adults from the Central African Republic

Abstract: T-cell ratio, 1.13 (males) and 1.41 (females). We concluded that (i) the WBC and hemoglobin values of healthy HIV-negative adults from the CAR are lower than the reference values currently used in the CAR and (ii) the absolute CD4 T-cell counts of healthy HIV-negative adults from the CAR are similar to values for Europeans but the absolute CD8 T-cell counts are much higher. Thus, the CD4/CD8 T-cell ratios for healthy adults from the CAR are significantly reduced compared to the ratios for healthy Europeans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
78
12
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 13 publications
29
78
12
1
Order By: Relevance
“…When we compare other published reference ranges for blood donors from Cameroon, and Central Africa the results are quite similar, with only a 5% difference in CD4+ T-lymphocytes count [20,21].…”
Section: Discussionsupporting
confidence: 49%
“…When we compare other published reference ranges for blood donors from Cameroon, and Central Africa the results are quite similar, with only a 5% difference in CD4+ T-lymphocytes count [20,21].…”
Section: Discussionsupporting
confidence: 49%
“…These gender differences in RBC parameters as illustrated in our findings (Table 2), are consistent with previously established evidence that males have higher values than females for these parameters and is partly attributed to the influence of the androgen hormone on erythropoiesis [43,44] and to menstrual blood loss in women [16,25,39,42,45]. It has been reported that estrogens lower the Hb through hemodilution while testosterone increases the plasma volume but increases circulating RBC to an even greater extent [46].…”
Section: Laboratory Reference Intervals In Africa 309supporting
confidence: 81%
“…(MCH) by gender have been observed in several African studies, with adult males having higher values than adult females in East Africa [9,16,20,31,39,40], Southern Africa [20,36], West Africa [41] and Central Africa [42]. These gender differences in RBC parameters as illustrated in our findings (Table 2), are consistent with previously established evidence that males have higher values than females for these parameters and is partly attributed to the influence of the androgen hormone on erythropoiesis [43,44] and to menstrual blood loss in women [16,25,39,42,45].…”
Section: Laboratory Reference Intervals In Africa 309mentioning
confidence: 99%
“…In HIV-negative Ugandan populations, women have higher absolute CD4 cell counts and percentages than men [27,28], as is seen in some other African populations (South Rift Valley, Kenya; Southern Highlands, Tanzania) [29,30], but not in all [31]. This pattern could also be the result of men having lower absolute CD4 cell counts and percentages at baseline than women.…”
Section: Discussionmentioning
confidence: 81%